Fractures of the Humeral Condyles in Children – A Review - Tepeneu, NF (Journal of Medical and Psychological Trauma, 2018)
The three most common elbow fractures classically reported in pediatric orthopedic literature are supracondylar (50–70%), lateral condylar (17–34%), and medial epicondylar fractures (10%). The mechanism of injury varies, but the most commonly described mechanism involves a fall on an outstretched hand with varus, valgus or rotational force or a combination thereof. The vectors of force and the degree of chondro-osseous development dictate the type of injury incurred. A review of the literature was conducted to see the most frequent injuries and complications.
Keywords: trauma; humerus; humeral condyle fracture; children